Effect of N,P,K Fertilizer Rate and Biofertilizer on Growth and Yield of IR42 Rice Paddy Variety - Suryadi, Cece; Budiasih, R.; Parlinah, Linlin (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
The research was carried out in the rice fields of Jaya Mukti Village, Blanakan District, Subang Regency, at an altitude of 10 meters above sea level. The experiment will be carried out from August 2022 to November 2022. This research aims to study the interaction effect of giving doses of N, P, K fertilizer and biological fertilizer on the growth and yield of lowland rice plants of the IR42 variety. This experiment used a Randomized Block Design (RAK) experimental design with a factorial pattern consisting of two factors, namely the first factor was N, P, K (p) fertilizer at 3 levels and the second factor was Biological Fertilizer (h) at 3 levels, both factors were repeated 3 times. There were 9 treatment combinations that were randomly assigned to each replication. The results of this research show that giving doses of N, P, K and biological fertilizers has an effect on growth (plant height at 21 DAP and number of tillers at 28 DAP), yield (grain weight per hill). The application of N, P, K fertilizer affects the yield components (number of productive tillers, panicle length and weight of 1000 grains). The N, P, K dose of 60% shows the best panicle length and weight of 1000 grains. Biofertilizer dosage of 30 kg ha -1 shows good results on plant height